CONSUMER PROTECTION IN THE DIGITAL ECONOMY: A LEGAL ANALYSIS OF E-COMMERCE PRACTICES AND REGULATORY CHALLENGES (Lex localis - Journal of Local Self-Government, 2025)
The growth of the digital economy has significantly reshaped consumer interactions, particularly in e-commerce, where users increasingly encounter risks related to data privacy, fraudulent activities, and imbalanced market practices. This qualitative literature review critically examines existing legal frameworks, academic discussions, and international policy developments to assess how effectively current regulations address these challenges. By analyzing diverse sources, the study finds that traditional consumer protection laws often fail to adapt to the complexities of digital commerce, especially in the context of cross-border transactions, platform responsibilities, and online dispute resolution. Significant concerns arise around transparency in digital contracts, protection of personal data across jurisdictions, and mechanisms that ensure consumer redress. The review also highlights promising regulatory innovations such as the European Union’s Digital Services Act and the General Data Protection Regulation, which represent a shift towards more robust and modernized consumer safeguards. However, inconsistencies in global enforcement and the lack of harmonized standards remain critical obstacles. The findings emphasize the urgent need for adaptive, integrated, and globally coordinated legal responses that balance technological innovation with the fundamental rights of consumers. This study contributes to ongoing legal and policy discourse by offering insights that support the development of more responsive and inclusive regulatory frameworks for consumer protection in the digital age.